Enhancing thermoelectric properties of p-type SiGe alloy through optimization of carrier concentration and processing parameters. (December 2018) - Wongprakarn, Suphagrid; Pinitsoontorn, Supree; Tanusilp, Sora-at; Kurosaki, Ken
Abstract: The enhancement in thermoelectric (TE) properties of p -type SiGe alloys through the optimization of carrier concentration and processing parameters was reported. The p -type Si80 Ge20 Bx alloys were prepared by melt spinning (MS) followed by spark plasma sintering (SPS). The effect of B concentration and processing parameters (rotating speed of Cu wheel in MS and holding time in SPS) was investigated. By adjusting the B content, the carrier concentration was notably changed but the carrier mobility was not significantly different. Consequently, TE properties were varied with B concentration and showed the optimum value for Si80 Ge20 B0.5 with the maximum ZT of 0.71 at 1073 K. Increasing the Cu wheel rotating speed resulted in the refined microstructure of the MS ribbons. The smaller grain sizes were maintained even after SPS. However, despite the refined grains, the TE properties were insignificantly different for any rotating speed. Reducing the SPS holding time resulted in bulk samples with lower density, presumably containing nano/micro porous structure. The presence of pores in the microstructure effectively reduced thermal conductivity due to a stronger phonon scattering, but also suppressed the electrical contribution making an obvious drop in the power factor. The optimized holding time for SPS was 5 min at 1323 K. Graphical abstract: fx1 Highlights: p -type SiGe alloys were successfully fabricated by melt spinning (MS) followed by spark plasma sintering (SPS). Carrier concentration was optimized resulting in the maximum ZT of 0.71 at 1073 K. Refined microstructure was obtained by increasing the rotating speed of the Cu wheel in the MS process. The holding time 5 min for SPS was recommended to ensure fully dense samples with maximum ZT .